POROUS MATERIAL ADSORBENTS IN ADVANCES DESIGN CONFIGURATION OF ADSORPTION DESALINATION PROCESS: A REVIEW - Riana Ayu Kusumadewi; Setyo Sarwanto Moersidik; Sucipta Laksono; Firdaus Ali; Nandy Putra; Shafira Budiningsih; Widi Ajeng Luthfiyya (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
Several desalination systems with distinct operational principles have been developed to enhance the generation of freshwater and optimize system efficiency. Adsorption desalination (AD) systems are highly desirable because to their ability to simultaneously achieve desalination and cooling using minimal energy input. These systems offer significant cost savings in terms of maintenance compared to conventional desalination systems. In order to gain a comprehensive understanding of the fundamental constituents of this desalination technology, the present study initially expounds upon the theory of adsorption and the process of circulation. Aims: The aim of this study is to conduct a thorough analysis of adsorbents for adsorption desalination and adsorption desalination technologies, and investigation into their potential integration with established conventional cycles, including multiple-effect distillation (MED), solar regenerable, and integrated evaporator-condenser cycles. Methodology and results: The findings of this study involve the evaluation and summarization of pertinent research on the fundamental aspects of the adsorption desalination system. These aspects include the thermodynamic process and cycle, performance assessment, adsorbents, and adsorption desalination technologies. The location, heat energy supply, collector, evaporator, condenser, adsorption desalination, adsorbent materials, and findings are investigated. Conclusion, significance and impact study: The discourse pertaining to prospective avenues of research, which will prove beneficial for analogous investigations within this domain, reaches a culmination.